KONSEP TRANSAKSI BAI’ATAINI FI BAI’AH DALAM FATWA BISNIS KONTEMPORER - Imam Kamaluddin; Mahmud; Bahrul Ulum; Ali Rahmat (Al-Mubin, 2022)
This research analyzes the bai'ataini fi bai'ah as one of the hybrid contract models prohibited in Islam through the hadith of the Prophet which strictly prohibits it. From the interpretation of the scholars about the meaning of bai'ataini fi bai'ah, it is found that various models of understanding of the meaning, model and form are found, but they converge on the two 'illat prohibitions namely the existence of gharar and riba. This paper argues that there is a looser opinion to avoid bai'ataini fi bai'ah so that the model of merging contemporary transactions required according to the times can be implemented without Islamic law.